The Emotional Classification of the Character Jia Xialing in the Film "Hallo! Mom" 2021《你好，李焕英 2021》: David Krech's Theory - Muhammad Farhan Masrur; Ziyu Jiang; Zalza Prabuditia Sabrina; Dwi Ari Tunggu Suweni (International Journal of Chinese Interdisciplinary Studies, 2023)
Abstract: The analysis of literary works provides profound insights into human character and experience, while also shedding light on cultural values and social transformations. The research utilizes internet browsing and literature review techniques with data collection, data analysis, and presentation of the analyzed data. The data is analyzed considering David Krech's classification theory of emotions, where the character's emotions are classified based on the theory and connected to the existing conflicts. Through quotes in the film, deep emotional experiences for Jia Xiaoling are depicted. The theory of social emotions and self-awareness can help understand the feeling of embarrassment experienced by Jia. This theory emphasizes the importance of emotional attachment between a child and their mother in shaping the child's emotional development.